Magnesium and posthypoxic changes of nitrergic population in rat hippocampus - Jandová, Kateřina; Riljak, Vladimír; Marešová, Dana; Langmeier, Miloš; Pokorný, Jaroslav (Prague Medical Report, 2010)
We used NADPH-diaphorase staining to study effects of magnesium pre-treatment during long-lasting hypoxia on the brain structure of rats. NADPH-diaphorase is an enzyme co-localized in neurons with NO-synthase that is responsible for NO synthesis. NO participates in hypoxic-ischaemic injury of the brain. Hypoxia was induced in consecutive days from the 2nd till the 11th day of postnatal life in a hypobaric chamber (for 8 hours per day). Magnesium was administered before each hypoxia exposition. At the age of 12 days, the animals were transcardially perfused with 4% buffered neutral paraformaldehyde under the deep thiopental anaesthesia. Cryostat sections were stained to identify NADPH-diaphorase positive neurons that were then quantified in five hippocampal regions. In comparison to the control animals, intermittent hypoxia brought about higher density of NADPH-diaphorase positive neurons in all studied areas of the hippocampal structure: in CA1 and CA3 areas of the hippocampus and in hilus, in the dorsal and ventral blades of the dentate gyrus. Magnesium pre-treatment during hypoxia reduced number of NADPH-diaphorase positive neurons in all studied areas.
Keywords: statistika jako téma; financování organizované; hořčík; Barotrauma; Evidence-Based Medicine; hipokampus; NADPH Dehydrogenase; Statistics as Topic; nitrergní neurony; Rats, Wistar; mužské pohlaví; Hypoxia-Ischemia, Brain; Animal Experimentation; NADPH-dehydrogenasa; barvení a značení; barotrauma; Financing, Organized; zvířata; Staining and Labeling; oxid dusnatý; mozková hypoxie a ischemie; Nitric Oxide; Magnesium; experimenty na zvířatech; medicína založená na důkazech; potkani Wistar; Nitrergic Neurons; Male; Hippocampus; Animals